A study of extrusion shear in the spinning of cellulose acetate hollow fiber membranes for reverse osmosis - Idris, Ani; Ismail, Ahmad Fauzi; Shilton, S. J. (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
The influence of dope extrusion rate on the morphology and performance of reverse osmosis hollow fibers were investigated. Hollow fiber reverse osmosis membranes were produced using a dry/wet spinning process with forced convection and spun at various shear rates ranging from 2.5 cm3/min to 5.0cm3/min. In this case, the residence time is fixed at 0.615s in order to decouple the shear effect from the forced convection effect. Separation performance of the hollow fibre membranes was evaluated using salt water of concentration 1000ppm at 100psig. Experimental results showed that a higher dope extrusion shear rate apparently resulted in a reverse osmosis hollow fibers with a thinner active layer. As a consequence, rejection rate of these membranes are increased. This may be the result of induced molecular orientation in the active layer. However a critical shear rate existed beyond which the rejection rate decreases. This was attributed to the development of surface pores as the active layer thins. Results suggested that it is possible to increase the performance of reverse osmosis hollow fibers by using the optimum shear rate. Hollow fibers with rejection rates as high as 95.5% could be produced with proper control in the rheological aspect.